Work Immersion Preparedness Among Senior High School Students: Industry Partners’ Perspective - Alcid, Agatha (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigates the work immersion preparedness of senior high school students as perceived by industry partners in Santiago City. Focusing on the Technical–Vocational and Academic strands, the research assesses students’ readiness across key workplace competencies, including punctuality, interpersonal relationships, productivity, efficiency, and safety. Using a descriptive survey design, 57 industry partners from selected public schools participated, providing evaluations of 66 student interns. Data were gathered through validated questionnaires and semi-structured interviews, with reliability confirmed via Cronbach’s alpha (ranging from .908 to .972). Findings indicate that students are generally prepared, with highest ratings in safety and interpersonal relationships and lower ratings in efficiency. Significant differences were observed among students grouped by strand, highlighting areas for strand-specific improvement. Industry partners identified challenges such as students’ lack of experience, insufficient skills, and engagement with non-productive activities. Based on these results, the study proposes a comprehensive school plan aimed at enhancing work immersion preparedness through targeted interventions, monitoring systems, and collaboration with industry partners. The research provides valuable insights for educators, administrators, and policy-makers to strengthen SHS work immersion programs and better equip students with employable skills for future careers.
Keywords: Work Immersion, Senior High School, Industry Partners, Student Preparedness, Workplace Competencies, Technical–Vocational Education